Molecular evolution of toothed whale genes reveals adaptations to echolocating in different environments - L. Magpali; E. Ramos; A. Picorelli; L. Freitas; M. F. Nery (BMC Genomics, 2024)
Abstract Background Echolocation was a key development in toothed whale evolution, enabling their adaptation and diversification across various environments. Previous bioacoustic and morphological studies suggest that environmental pressures have influenced the evolution of echolocation in toothed whales. This hypothesis demands further investigation, especially regarding the molecular mechanisms involved in the adaptive radiation of toothed whales across multiple habitats. Here we show that the coding sequences of four hearing genes involved in echolocation (CDH23, prestin, TMC1, and CLDN14) have different signatures of molecular evolution among riverine, coastal, and oceanic dolphins, suggesting that the evolutionary constraints of these habitats shaped the underlying genetic diversity of the toothed whale sonar. Results Our comparative analysis across 37 odontocete species revealed patterns of accelerated evolution within coastal and riverine lineages, supporting the hypothesis that shallow habitats pose specific selective pressures to sonar propagation, which are not found in the deep ocean. All toothed whales with genes evolving under positive selection are shallow coastal species, including three species that have recently diverged from freshwater lineages (Cephalorhynchus commersonii, Sotalia guianensis, and Orcaella heinsohni - CDH23), and three species that operate specialized Narrow Band High Frequency (NBHF) Sonars (Phocoena sinus - prestin, Neophocaena phocaenoides - TMC1 and Cephalorhynchus commersonii - CDH23). For river dolphins and deep-diving toothed whales, we found signatures of positive selection and molecular convergence affecting specific sites on CDH23, TMC1, and prestin. Positively selected sites (PSS) were different in number, identity, and substitution rates (dN/dS) across riverine, coastal, and oceanic toothed whales. Conclusion Here we shed light on potential molecular mechanisms underlying the diversification of toothed whale echolocation. Our results suggest that toothed whale hearing genes changed under different selective pressures in coastal, riverine, and oceanic environments.